Cross-reactive neutralizing human monoclonal antibodies mapping to variable antigenic sites on the norovirus major capsid protein - Ford-Siltz, Lauren A.; Tohma, Kentaro; Alvarado, Gabriela S.; Kendra, Joseph A.; Pilewski, Kelsey A.; Crowe, James E.; Parra, Gabriel I. (Frontiers in Immunology, 2022)
Human noroviruses are the major viral cause of acute gastroenteritis around the world. Although norovirus symptoms are in most cases mild and self-limited, severe and prolonged symptoms can occur in the elderly and in immunocompromised individuals. Thus, there is a great need for the development of specific therapeutics that can help mitigate infection. In this study, we sought to characterize a panel of human monoclonal antibodies (mAbs; NORO-123, -115, -273A, -263, -315B, and -250B) that showed carbohydrate blocking activity against the current pandemic variant, GII.4 Sydney 2012. All antibodies tested showed potent neutralization against GII.4 Sydney virus in human intestinal enteroid culture. While all mAbs recognized only GII.4 viruses, they exhibited differential binding patterns against a panel of virus-like particles (VLPs) representing major and minor GII.4 variants spanning twenty-five years. Using mutant VLPs, we mapped five of the mAbs to variable antigenic sites A (NORO-123, -263, -315B, and -250B) or C (NORO-115) on the major capsid protein. Those mapping to the antigenic site A showed blocking activity against multiple variants dating back to 1987, with one mAb (NORO-123) showing reactivity to all variants tested. NORO-115, which maps to antigenic site C, showed reactivity against multiple variants due to the low susceptibility for mutations presented by naturally-occurring variants at the proposed binding site. Notably, we show that cross-blocking and neutralizing antibodies can be elicited against variable antigenic sites. These data provide new insights into norovirus immunity and suggest potential for the development of cross-protective vaccines and therapeutics.